Features of the Development of the Intellectual Potential of the Primary School Student - Dilbar Kadirova Termez; Majitova Aziza Musurmankulovna (Research Parks Publishers, 2021)
This article describes the most important achievements in the development of primary school students in the context of educational activities and provides information on which new psychological structures will be decided, which will be the basis for development in the next age. Under the influence of teaching, a reconstruction of all cognitive processes takes place in primary school students. This is a period of rapid development and qualitative change of these young cognitive processes, which are of an indirect nature and are understood and voluntary. Students gradually begin to master their own mental processes, learning to control attention, memory, thinking.